2011
DOI: 10.1111/j.1751-7176.2011.00522.x
|View full text |Cite
|
Sign up to set email alerts
|

Neurovascular Decompression of the Rostral Ventrolateral Medulla Decreases Blood Pressure and Sympathetic Nerve Activity in Patients With Refractory Hypertension

Abstract: 7Recently, the authors experienced four patients who had refractory hypertension and neurovascular compression of the rostral ventrolateral medulla (RVLM). One of them, a 49-year-old woman, had undergone continuous intravenous drip injections of calcium channel blockers and b-blockers for more than 3 years because of severe and refractory hypertension. The patients had undergone microvascular decompression (MVD) of the RVLM, and the changes in blood pressure (BP) and sympathetic nerve activities were recorded.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 8 publications
1
15
0
1
Order By: Relevance
“…Több, hypertoniás betegek körében végzett vizsgálatban a plazma noradrenalinszintje igazolt NVC esetén magasabb volt a kontrollcsoporthoz képest [8,9]. Japán munkacsoport 4, NVC miatt műtött betegnél műtét után a vérnyomáscsökkenés mellett a n. tibialis szimpatikus aktivitásának csökkené-sét, a vizelet adrenalinszintjének csökkenését igazolta a műtét előtti értékhez képest [10].…”
Section: Esetismertetésunclassified
“…Több, hypertoniás betegek körében végzett vizsgálatban a plazma noradrenalinszintje igazolt NVC esetén magasabb volt a kontrollcsoporthoz képest [8,9]. Japán munkacsoport 4, NVC miatt műtött betegnél műtét után a vérnyomáscsökkenés mellett a n. tibialis szimpatikus aktivitásának csökkené-sét, a vizelet adrenalinszintjének csökkenését igazolta a műtét előtti értékhez képest [10].…”
Section: Esetismertetésunclassified
“…Ten of 12 patients experienced reduction in systolic blood pressure of more than 20 mm Hg. Sasaki et al 35 decompressed the RVLM in 4 patients with refractory hypertension. All 4 patients had decreased sympathetic nerve activity after the decompression and normalization of blood pressure without any antihypertensive medication.…”
Section: 43mentioning
confidence: 99%
“…Compression of this center might yield a heightened sympathetic tone, leading to AH. 2,7,12,25,29,35 Jannetta et al [17][18][19] demonstrated that microvascular decompression (MVD) of the RVLM could normalize or improve a raised blood pressure. Because the RVLM is close to the origin of the facial nerve, vessel loops originating from the vertebral/basilar arteries might be responsible for multiple neurovascular compressions (NCs), inducing both hemifacial spasms (HFSs) and AH.…”
Section: 14mentioning
confidence: 99%
“…This concept has been confirmed by autopsy, MRI, intraoperative observation, and animal studies. 5 MRI, computed tomography, and angiography have been used to assess neurovascular compression of the RVLM. To date, MRI is the most effective method for studying details of the brainstem and the surrounding vessels involved in neurovascular compression because of its noninvasiveness and sensitiveness.…”
mentioning
confidence: 99%